Audit Sistem Informasi Akademik (SIMAK) Menggunakan Framework COBIT 5 di Universitas Universal - Riani, Eva; Yonathan, Jeremy; Oliver, Leaonardi (Journal of Digital Ecosystem for Natural Sustainability, 2021)
The use of technology has now been applied by almost all sectors of job, one of which is in the field of education. Information management at Universal University using the Academic Information System has been implemented for approximately 4 (four) years since 2017. However, so far SIMAK at Universal University has never conducted any evaluation or audit of IT governance, so the use of SIMAK has not been proven whether has been going well, therefore it is necessary to conduct an IT Governance Audit at Universal University on SIMAK services using the COBIT 5 framework MEA (Monitor, Evaluate and Assess) domain. The results show that the SIMAK capability level at Universal University is currently at level 1 (Performed Process) which means that the system has been running well and the IT goals have been achieved. SIMAK at Universal University has not yet reached the expected condition (To Be), which is at level 4 (Predictable Process) with the gap it has is 3.